ভাষাংশসংগ্রহ ও আধুনিক ভাষাবিজ্ঞান - Niladri Sekhar Dash (Dakshabharati, 2006)
This is the first book in Bengali on corpus linguistics. It tells the readers about how it is possible to make a corpus written in Bengali using a practical sample of the language for various purposes in theoretical and practical linguistics and language technology.
Bhasanshasamgraha o Adhunik Bhashabijnan (Language Corpora and Modern Linguistics)
Keywords: Bengali; Linguistics; Bengali; Bengali